2005
DOI: 10.1158/1078-0432.ccr-04-1765
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 Expression is Associated with Poorer Response to Radiation and Shorter Overall Survival in Glioblastoma

Abstract: Purpose: YKL-40 is a secreted protein that has been reported to be overexpressed in epithelial cancers and gliomas, although its function is unknown. Previous data in a smaller sample set suggested that YKL-40 was a marker associated with a poorer clinical outcome and a genetically defined subgroup of glioblastoma. Here we test these findings in a larger series of patients with glioblastoma, and in particular, determine if tumor YKL-40 expression is associated with radiation response. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
179
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(205 citation statements)
references
References 44 publications
19
179
1
1
Order By: Relevance
“…Immunohistochemical analysis was performed as described previously. 17 Formalin-fixed and paraffin-embedded tissue sections (2 lm) were deparaffinized stepwise in xylene and rehydrated in graded solutions of ethanol (100%, 95%, and 80%, respectively) followed by phosphatebuffered saline (PBS) and 0.1 mol/L Tris buffer (pH 8.0). Antigen retrieval was performed at 95 C for 40 minutes using 0.01 M sodium citrate buffer (pH 6.0).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analysis was performed as described previously. 17 Formalin-fixed and paraffin-embedded tissue sections (2 lm) were deparaffinized stepwise in xylene and rehydrated in graded solutions of ethanol (100%, 95%, and 80%, respectively) followed by phosphatebuffered saline (PBS) and 0.1 mol/L Tris buffer (pH 8.0). Antigen retrieval was performed at 95 C for 40 minutes using 0.01 M sodium citrate buffer (pH 6.0).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Identification of staining pattern was performed using a modified 2-tiered system as previously described. 17 The most distinctive areas were picked up for this scoring system and subsequently dichotomized into total-Nurr1-high versus total-Nurr1-low or cytoplasmic-Nurr1-high versus cystoplasmic-Nurr1-low.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Samples, for which no threshold cycle could be determined, were excluded for that particular gene. Values of CHI3L2, IL1B, EGLN3, APOC1 and PI3 were compared with those of CHI3L1, which encodes for the poor prognosis marker YKL-40 22 using nonparametric Spearman's correlation. To determine whether expression of the selected genes differs FIGURE 1 -Biological effects of vascular endothelial growth factor (VEGF) siRNA in U87 glioma cells in vitro (a) Three different small interfering RNAs (siRNAs) targeting VEGF-A were designed.…”
Section: Gene Expression Correlation and Survival Analysismentioning
confidence: 99%
“…77,80,93,102 Furthermore, mutation of PTEN, a 10q gene, has also been correlated with poor prognosis. 28,99 Additional molecular markers predicting a negative prognosis for patients with astrocytic gliomas have included the following: loss of chromosome 9p or CDKN2A deletion, 80 gains of 7p and 7q, 57 activated phosphatidylinositol 3-kinase, 21 YKL-40, 78 and a dysfunctional RB pathway. 2 Furthermore, CGH 13,57,117 and gene expression profiling 62,87 have also provided novel sources of prognostic information.…”
Section: Role Of Molecular Genetics In Clinical Management Of Astrocymentioning
confidence: 99%
“…78 Most recently, EGFR status has been investigated in astrocytic gliomas treated with erlotinib, a small-molecule inhibitor of EGFR. One study demonstrated that tumors with high levels of EGFR expression and low levels of phosphorylated PKB/Akt responded better to erlotinib than lesions with low levels of EGFR and high levels of phosphorylated PKB/Akt.…”
Section: -61mentioning
confidence: 99%